Using Respiratory Sinus Arrhythmia to Estimate Inspired Tidal Volume in the Bottlenose Dolphin (Tursiops truncatus) - Cauture, Fabien; Sterba-Boatwright, Blair; Rocho-Levine, Julie; Harms, Craig; Miedler, Stefan; Fahlman, Andreas (Frontiers in Physiology, 2019)
Man-made environmental change may have significant impact on apex predators, like marine mammals. Thus, it is important to assess the physiological boundaries for survival in these species, and assess how climate change may affect foraging efficiency and the limits for survival. In the current study, we investigated whether the respiratory sinus arrhythmia (RSA) could estimate tidal volume (VT) in resting bottlenose dolphins. For this purpose, we measured respiratory flow and electrocardiogram (ECG) in five adult bottlenose dolphins (Tursiops truncatus) at rest while breathing voluntarily. Initially, an exponential decay function, using 3 parameters (baseline heart rate, the change in heart rate following a breath, and an exponential decay constant) was used to describe the temporal change in instantaneous heart rate following a breath. The three descriptors, in addition to body mass, were used to develop a Generalized Additive Model (GAM) to predict the inspired tidal volume (VTinsp). The GAM allowed us to predict VTinsp with an average (± SD) overestimate of 3% ± 2%. A jackknife sensitivity analysis, where 4 of the 5 dolphins were used to fit the GAM and the 5th dolphin used to make predictions resulted in an average overestimate of 2% ± 10%. Future studies should be used to assess whether similar relationships exist in active animals, allowing respiratory health and VT to be studied in free-ranging animals provided that heart rate can be measured.